#### Answer

-1

#### Work Step by Step

$-(3)^{0}$
=(-1)(1)
=-1
Remember that anything to the 0 power equals 1

Published by
Prentice Hall

ISBN 10:
0133281140

ISBN 13:
978-0-13328-114-9

-1

$-(3)^{0}$
=(-1)(1)
=-1
Remember that anything to the 0 power equals 1

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.